2014
DOI: 10.1007/s00221-014-3972-3
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of spontaneous movements of infants as combinations of limb synergies

Abstract: We hypothesized that a variety of limb movements in infants, including spontaneous movements and movements during interactions with the environment, can be represented as combinations of limb synergies, which are building blocks for generating coordinated movements of multiple limbs. A decomposition algorithm based on a nonnegative matrix factorization was applied to the discrete data segments taken from continuous data of limb movements in 298 infants (age, 3-4 months). The data were linearly decomposed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…This suggests the importance of understanding the development of rolling not as a change from one pattern to another but rather as a change from one set of patterns to another set of patterns. Previous studies showed the complex patterns of spontaneous in infants (Watanabe and Taga 2011;Kanemaru et al 2012;Kato et al 2013Kato et al , 2014Ohmura et al 2016). However, distinguishing individual variability from intra-individual variability is challenging.…”
Section: Limitations and Future Issuesmentioning
confidence: 98%
“…This suggests the importance of understanding the development of rolling not as a change from one pattern to another but rather as a change from one set of patterns to another set of patterns. Previous studies showed the complex patterns of spontaneous in infants (Watanabe and Taga 2011;Kanemaru et al 2012;Kato et al 2013Kato et al , 2014Ohmura et al 2016). However, distinguishing individual variability from intra-individual variability is challenging.…”
Section: Limitations and Future Issuesmentioning
confidence: 98%
“…NMF can decompose the multi-joint velocities for limb movement into two components: the time-invariant kinematic synergies combining by all joints with different weightings, and the time-varying activation coefficients representing the activation patterns of corresponding synergies [ 22 , 26 ]. Kato et al successfully employed the NMF algorithm to derive kinematic synergies from the tangential velocities of joints of the four limbs for spontaneous movements of infants, where these synergies represented the dominance of different combinations of limbs [ 27 ]. Since the tangential velocities of joints do not include the direction of limb movement in space, the analytical complexity of limb movement can be highly reduced [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al successfully employed the NMF algorithm to derive kinematic synergies from the tangential velocities of joints of the four limbs for spontaneous movements of infants, where these synergies represented the dominance of different combinations of limbs [ 27 ]. Since the tangential velocities of joints do not include the direction of limb movement in space, the analytical complexity of limb movement can be highly reduced [ 27 , 28 ]. Although our pilot study has preliminarily distinguished infants with MDD from typically developing (TD) infants by the kinematic synergies of tangential velocities of joints during crawling [ 29 ], it is less clear how MDD affects interlimb coordination based on those synergies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, quantitative analysis of arm-leg coordination has been performed in neonates' stepping and demonstrated a neural coupling between the arms and legs ( 13 ). Then, spontaneous movements around 2 months have been shown to display some primitive forms of coordinative behavior between arms and legs ( 14 ). Much later, at approximately the age of 9 months, infant's creeping behavior begins with the clumsy attempts to move forward with the abdomen touching the ground.…”
Section: Introductionmentioning
confidence: 99%